A Comparative Study of Extrovert and Introvert Students in Storytelling Performance on Speaking Ability at The Eleventh Grade Students of Smks Ywka Medan - Agnesia Yohana M Purba; Lastri Wahyuni Manurung; Ernawati Tampubolon (Visi Sosial Humaniora, 2026)
Purba Agnesia Yohana M 22120069.2026 A Comparative Study of Extrovert and Introvert Students in Storytelling Performance on Speaking Ability at the Eleventh Grade Students of Smks Ywka Medan.Thesis. Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan Dan Ilmu Pendidikan Universitas HKBP Nommensen Medan. This study aimed to compare the storytelling performance in speaking ability between extrovert and introvert students at the eleventh grade of SMKS YWKA Medan. Storytelling is an important activity in developing students’ speaking skills, and personality type is believed to influence students’ performance in oral communication. This research employed a quantitative approach with a causal-comparative research design. The population of this study consisted of all eleventh-grade students of SMKS YWKA Medan in the academic year 2025/2026, totaling 51 students. The sample was selected using purposive sampling and consisted of 28 students from two classes. The Eysenck Personality Inventory (EPI) questionnaire was used to identify students’ personality types, while a storytelling speaking test was administered to measure students’ speaking performance. The storytelling performances were assessed by two raters using a speaking rubric covering pronunciation, fluency, vocabulary, expression, confidence, and content organization. The data were analyzed using descriptive statistics and an independent-samples t-test with SPSS version 26. The results of the study showed that there was a significant difference in storytelling performance between extrovert and introvert students, in which extrovert students tended to achieve higher speaking performance scores than introvert students. Therefore, it can be concluded that personality type has a significant influence on students’ storytelling performance in speaking ability.